A Novel Method Defends against the Path-Based DoS for Wireless Sensor Network - Dong Chen; Zhenjiang Zhang; Fan-Hsun Tseng; Han-Chieh Chao; Li-Der Chou (International Journal of Distributed Sensor Networks)
WSNs are significantly different from the traditional network architecture due to its wireless communication, energy limitation, and computation constraint and environment of the application. Because of these differences, security becomes a critical issue. The path-based denial of service (PDoS) attacks harm the network maintenance and cause serious damage in the resource constrained WSNs. In a PDoS attack, an adversary can overwhelm sensor node and cluster head node to flood packets along the routing path so that intermediate node must keep active mode and exhaust the energy. In this paper, we creatively propose a novel method, which is operated at the base station to detect the malicious behavior. The proposed method is combined with triple exponential smoothing and Markov chain, so that it makes the detection results more accurate. Meanwhile, we first use the concept of black hole to defend the PDoS attack in WSNs. Simulation results are provided to evaluate the performance and illustrate the contribution of this mechanism.